Schema.org para representação nos catálogos digitais: a descoberta de recursos informacionais na Web - Machado, Dayane Onaga Ferreira (Universidade Federal de São Carlos, 2022)
Introduction: The web search engines provide access to the multitude of available information, with dynamic, accurate and visually enriched results. Due to these characteristics, contemporary users are used to the practicality and dynamism offered by open and intuitive environments such as the Web. It is necessary to rethink the descriptive treatment in the catalogs since the architecture of the current software available for libraries and the communication protocols used do not allow interoperability with search engines or with other sources of information external to the bibliographic domain. In contrast, the Web offers a set of technologies focused on discovery and communication between different domains, one of these technologies is the Schema.org vocabulary. Objective: The objective of the research is to analyze Schema.org as an alternative for representing informational resources in catalogs, identifying the main characteristics and possible benefits and challenges of vocabulary adherence in the context of libraries. Methodological procedures: This study is theoretical in nature, carried out from a qualitative approach. From the point of view of the objectives, it is characterized as descriptive and in relation to the technical procedures, as bibliographic and documentary, aiming to explore the intersection between the themes, digital catalogs and Schema.org. Results: It was identified that the vocabulary has limitations for representation in specific domains, as in the case of libraries. However, the guidelines and structure of Schema.org are flexible, allowing the development of extensions, the classes, properties, and relationships can be adapted for representation in different contexts. Schema.org vocabulary can be used with encodings recommended by the World Wide Web Consortium (W3C) for structured data. In this way, it is possible to discover information in Rich Snippets and integrate the data into the Knowledge Graph. With these technologies, search results are enriched with additional elements. It was identified that in the bibliographic universe, Schema.org was included in the Online Computer Library Center projects and aligned with Linked Data principles for structuring and discovering WorldCat records. Conclusion: It is considered that the adherence of Schema.org together with the representation instruments developed within the scope of libraries can favor the exposure of catalog data on the Web. Thus, in addition to benefiting from technologies aligned with the scope of the Semantic Web, libraries can contribute to its development by sharing structured, relevant, and reliable information.
Schema.org for representation in digital catalogs: the discovery of information resources on the Web
Keywords: Catálogo digital; Catálogo de acesso público online; OPAC; Digital catalog; Online Public Access Catalog; Schema.org; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO